Life on the Brink : Environmentalists Confront Overpopulation - Crist, Eileen, 1961-; Cafaro, Philip, 1962- (Book collections on Project MUSE., 2012)
Life on the Brink aspires to reignite a robust discussion of population issues among environmentalists, environmental studies scholars, policymakers, and the general public. Some of the leading voices in the American environmental movement restate the case that population growth is a major force behind many of our most serious ecological problems, including global climate change, habitat loss and species extinctions, air and water pollution, and food and water scarcity. As we surpass seven billion world inhabitants, contributors argue that ending population growth worldwide and in the United States is a moral imperative that deserves renewed commitment. Hailing from a range of disciplines and offering varied perspectives, these essays hold in common a commitment to sharing resources with other species and a willingness to consider what will be necessary to do so. In defense of nature and of a vibrant human future, contributors confront hard issues regarding contraception, abortion, immigration, and limits to growth that many environmentalists have become too timid or politically correct to address in recent years. Ending population growth will not happen easily. Creating genuinely sustainable societies requires major change to economic systems and ethical values coupled with clear thinking and hard work. Life on the Brink is an invitation to join the discussion about the great work of building a better future.